2023
DOI: 10.4108/eetsc.v7i2.2925
|View full text |Cite
|
Sign up to set email alerts
|

Propaganda Detection And Challenges Managing Smart Cities Information On Social Media

Abstract: Misinformation, false news, and various forms of propaganda have increased as a consequence of the rapid spread of information on social media. The Covid-19 spread deeply transformed citizens' day-to-day lives due to the overview of new methods of effort and access to facilities based on smart technologies. Social media propagandistic data and high-quality information on smart cities are the most challenging elements of this study. As a result of a natural language processing perspective, we have developed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In their work, ref. [22] worked on bi-lingual dataset of tweets related to Smart City in Urdu and English. The authors have reported the best results using a fine-tuned RoBERTa model.…”
Section: Related Workmentioning
confidence: 99%
“…In their work, ref. [22] worked on bi-lingual dataset of tweets related to Smart City in Urdu and English. The authors have reported the best results using a fine-tuned RoBERTa model.…”
Section: Related Workmentioning
confidence: 99%
“…This study provides important practical implications for information technology societies struggling to improve information system expert defensive performances. First, the feature set contains almost all the features used in the related literature, such as identifying misinformation [3,44], political bias, clickbait, and satire. There is a great deal of early research in automatically identifying different writing styles and propaganda techniques employed by news sources [11].…”
Section: Practical Implicationmentioning
confidence: 99%
“…When a news organization's voice is heard by the public, it is a significant win because it raises the bar for freedom of speech and makes it possible for anybody to be heard. The news is inaccurate, spreads phony stories, and is propagandistic because of freedom of speech [3]. The reader needs to be well-versed in the subject area to spot propaganda.…”
Section: Introductionmentioning
confidence: 99%